Genetics Insight for COVID-19 Susceptibility and Severity: A Review - Fricke-Galindo, Ingrid; Falfán-Valencia, Ramcés (Frontiers in Immunology, 2021)
Coronavirus disease (COVID-19) presents a broad spectrum of clinical manifestations ranging from an asymptomatic to a severe clinical course. The host genetic background influence on the susceptibility and outcome of multiples infectious diseases has been previously reported. Herein, we aimed to describe relevant identified genetic variants and those potentially related to the inter-individual variability of COVID-19 susceptibility and/or severity considering the physiopathological pathway of the disease The HLA-A*25:01, -B*15:27, -B*46:01, -C*01:02, and -C*07:29 alleles have been associated with COVID-19 susceptibility; while HLA-A*02:02, -B*15:03, and -C*12:03 have been identified as low-risk alleles. Variants in cytokine genes such as IL1B, IL1R1, IL1RN, IL6, IL17A, FCGR2A, and TNF could be related to disease susceptibility and cytokine storm, and/or COVID-19 complications (e.g., venous thrombosis). Several variants in ACE2 and TMPRSS2 affecting the expression of the receptors related to COVID-19 have been associated with the disease susceptibility and risk factors. Finally, two GWAS have identified the loci 3p21.31 (LZTFL1, SLC6A20, CCR9, FYCO1, CXCR6, and XCR1) and 9q34.2 (ABO) with COVID-19 severity. Heterogeneous results in the association of genetic variants with COVID-19 susceptibility and severity were observed. The mechanism of identified risk-genes and studies in different populations are still warranted.